NARASI KOMUNIKASI PEREMPUAN YANG MENGALAMI KDRT (KEKERASAN DALAM RUMAH TANGGA) DALAM MEMUTUSKAN HUBUNGAN PERNIKAHAN - Aqila Nur Iswahyudi, Shima; Dwiningtyas Sulistyani, Hapsari; Suryanto Gono, Joyo Nur (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Until now, many cases of domestic violence (domestic violence) still occur among women in Indonesia. According to CATAHU Komnas Perempuan and KemenPPA, violence against women most often occurs in the domestic sphere or in the household. Abused women often find it difficult to end the relationship even though they know and feel the impact of the violence that their spouses do to them. Therefore, this research aims to analyze the stories of women who experience domestic violence in overcoming obstacles and difficulties in breaking off a marriage relationship until successfully leaving the relationship. This research is a qualitative research that utilizes Todorov's narrative method by conducting interview upon three women who experienced domestic abuse and had left the marriage. The results of this study reveal that since before marriage, every partner of the informants used destructive aggressive communication that caused informants to receive emotional and physical abuse when they did not do things as their partners told them to. However, the informants decided to stay and get married because three things, they already felt in love with their partners, did not want to fail again in a relationship, and got pushed by their parents who were already fond of the partner's background. Aggressive communication patterns recurred in the informants' marriages. Moreover, the violence they experienced also escalated. However, they still decided to stay in the marriage. At this point, the informants had entered a cycle of domestic violence because the informants eventually normalized the abuse that they received, had a positive perception of marriage after having a discussion with a friend and received repeated persuasion efforts from their spouses. The process of dissoluting the relationship began after the informants felt dissatisfied towards the communication proccess in a conflict with their partner that caused relationship dissatisfaction. Informants then reported the domestic violence to the police, took care of the divorce, and asked the husband to leave the house. Then, two informants will experience dialectical proccess which resulted in tension and negotiations to fix the relationship. When two informants' spouses did not fulfill the negotiation condition, the process of relationship dissolution finally continued. One informant used avoidance and manipulation strategies when her husband refused to end the relationship. This informant eventually continued the divorce process. The other two informants who were initially still waiting for their husbands' resolution efforts tried to fight the urge to stay and finally take care of the divorce. The other two informants used negative identity management strategies to communicate their desire to divorce and end their marriage. After the divorce process was completed, the three informants finally focused on building a better life by doing positive activities.